Evaluation of Mg/Al Layered Double Hydroxides as Adsorbent Material for Adsorptive Removal of Congo Red (Acid Red 28) Azodye from Aqueous Solution - Van Tan, Lam; Tham Nguyen Thi, Hong; Uyen Dao Thi, To; Thuan Tran, Van (Asian Journal of Chemistry, 2020)
The use of inorganic layer compounds as adsorbents for organic dyes in water treatment is of increasing interest. In this study, an attempt is made for the synthesis of Mg/Al LDHs by the hydrothermal method. The synthesis temperature was found to significantly affect to the structure of layered double hydroxides (LDHs), as pointed out by FT-IR analysis. In addition, an adsorption capacity of the synthesized LDHs against Congo red in aqueous solutions was investigated and also compared the adsorption results with other dyes such as methylene blue and methyl orange.